(untitled) - Moncure, Jane Belk; Thornburgh, Rebecca McKillip (Mankato, MN, 2009)
Labeled drawings show the eyes, nose, mouth, hair, feet, toes, friends, balloons, hats, pajamas, bed, cup, plate, apple, cookies, ball, wagon, doll, and blocks.
Keywords: Vocabulary